2015
DOI: 10.1111/jcmm.12557
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 reduction causes renal and retinal injury in diabetes through endothelin 1 and transforming growth factor β1

Abstract: In diabetes, hyperglycaemia causes up-regulation of endothelin 1 (ET-1) and transforming growth factor beta 1 (TGF-β1). Previously we showed glucose reduces sirtuin1 (SIRT1), a class III histone deacetylase. Here, we investigated the regulatory role of SIRT1 on ET-1 and TGF-β1 expression. Human microvascular endothelial cells were examined following incubation with 25 mmol/l glucose (HG) and 5 mmol/l glucose (NG) with or without SIRT1 or histone acetylase p300 overexpression or knockdown. mRNA expressions of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 29 publications
0
36
0
Order By: Relevance
“…The effects of SIRT1 polymorphisms on susceptibility to DN might be mediated by differences in the metabolic state among individuals, including glycemic control, obesity, blood pressure, respectively 25 27 . The evidence in Wild-type (C57BL/6 J) and SIRT1 transgenic mice (C57BL/6-Actb tm3.1(Sirt1)Npa /J) showed SIRT1 mediated protection against renal and retinal injury in DN 28 . FOXO1, as an important target for insulin and growth factor signaling, has been reported to play key roles in regulating metabolism, cell proliferation, cell cycle, apoptosis and oxidative stress response by regulating the expression of functionally important target genes 29 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The effects of SIRT1 polymorphisms on susceptibility to DN might be mediated by differences in the metabolic state among individuals, including glycemic control, obesity, blood pressure, respectively 25 27 . The evidence in Wild-type (C57BL/6 J) and SIRT1 transgenic mice (C57BL/6-Actb tm3.1(Sirt1)Npa /J) showed SIRT1 mediated protection against renal and retinal injury in DN 28 . FOXO1, as an important target for insulin and growth factor signaling, has been reported to play key roles in regulating metabolism, cell proliferation, cell cycle, apoptosis and oxidative stress response by regulating the expression of functionally important target genes 29 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Although chronic hyperglycemic environments can facilitate chromatin remodeling by histone methylation, histone acetylation can also significantly contribute to chromatin state dynamics. Former studies from our laboratory have indicated that the upregulation of histone acetyltransferase p300 can cause increased EDN1 promoter activity (Chen et al 2009), reduced expression of the class II histone deacetylase SIRT1 (Mortuza et al 2015), and increased expressions of ET-1 transcripts, extracellular matrix (ECM) proteins and vasoactive factors (Chen et al 2009. Collectively, our past and current findings demonstrate that pathologies like diabetes can cause unique alterations in histone modification patterns, which may ultimately enhance EDN1 transcriptional activity and contribute to elevated ET-1 protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…At the transcriptional level, regulating the production of downstream transcriptional factors is a major mechanism in the genesis of downstream effects . We have previously shown that alterations in epigenetic modifications such as histone acetylation and specific microRNAs (miRs) can affect this transcriptional regulation and mediate glucose‐induced abnormalities . Nevertheless, the transcriptional process can also be controlled by long noncoding RNAs (lncRNAs) …”
Section: Introductionmentioning
confidence: 99%